2011
DOI: 10.4236/aces.2011.13018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Dodecyl Sulphate on the Composition of Electroless Nickel – Yttria Stabilized Zirconia Coatings

Abstract: The influence of a surfactant on the composition of nickel-yttria stabilised zirconia (YSZ) cermet coatings, applied by electroless nickel plating technique was examined. The amphiphilic characteristics of anionic surfactant sodium dodecyl sulphate (SDS), was relied upon for enhanced dispersion of YSZ particles co-deposited for use as anodes in solid oxide fuel cell technology and potential heat absorbing layers in thermal barrier coatings. Optical microscopy was employed to study the correlation between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…10,11 Also, using suitable surfactants greatly affects the uniform distribution of particles in the composite coatings. 12,13 In recent years, several investigations have been performed on hard and soft particles such as ceramics and polymers, 14–18 but there is a few information about the hardening mechanisms of composite coatings. Alumina as a common hard material with significant properties has been paid more attention among other hard particles in electroless composite coatings.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Also, using suitable surfactants greatly affects the uniform distribution of particles in the composite coatings. 12,13 In recent years, several investigations have been performed on hard and soft particles such as ceramics and polymers, 14–18 but there is a few information about the hardening mechanisms of composite coatings. Alumina as a common hard material with significant properties has been paid more attention among other hard particles in electroless composite coatings.…”
Section: Introductionmentioning
confidence: 99%
“…66 This result interestingly correlates well with the findings from our previous work where with the introduction of 0.9 g L −1 SDS, up to 60% by volume, yttria stabilized zirconia (YSZ) was incorporated into the nickel matrix. 83 Zhou and co-workers also found that 50 mg L −1 of anionic surfactants SDBS and SDS, and 100 mg L −1 of the surfactant triethanolamine, yielded good results during the codeposition of nano Al 2 O 3 particulate matter. 22 Three different types of flourosurfactants were utilized by Amell et al 67 during the codeposition of SiC and Si 3 N 4 particles.…”
Section: Influence On Coatingsmentioning
confidence: 95%
“…Nwosu et al (16) conclusively found that as long as the SDS surfactants critical micelle concentration had been exceeded, the ceramic content of a co-deposited nickel / YSZ electrode had a direct relationship with the surfactants concentration in the bath. Local concentrations of ceramic to nickel ratios as high as 60 volume % were achieved.…”
Section: Bath Chemistry (Surfactants Ph)mentioning
confidence: 99%